Yube: um percurso de criação - Florentino, Juliana Paula [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
This academic work in arts developed a art piece that proposed an approximation with the Brazilian indigenous culture, in which the technique of embroidery on fabric was used. It was discussed how the techniques of weaving and embroidery emerged in prehistory, how the textile craft was socially constructed as a feminine work and how it fit into the artistic realm. Regarding the references for the production of the work, the work is shown in elements present in the Brazilian Amazon Forest, such as Elsje Lagrou's ethnography about the Huni Kuin people and the production of the artist Margaret Mee. In the account of the creation process were presented the stages of the production of the work

Este trabalho em artes desenvolveu uma obra que propôs uma aproximação com a cultura indígena brasileira, na qual foi utilizada a técnica do bordado sobre tecido. Abordou-se como as técnicas da tecelagem e do bordado surgiram na pré história, de que maneira o ofício têxtil foi socialmente construído como um labor feminino e de que forma se inseriu no âmbito artístico. A respeito dos referenciais para produção da obra, o trabalho se pautou em elementos presentes na Floresta Amazônica brasileira tais como a etnografia de Elsje Lagrou a respeito do povo Huni Kuin e a produção da artista inglesa Margaret Mee. No relato do processo de criação foram apresentadas as etapas da produção da obra
Keywords: Mee, Margaret 1909-1988; Trabalhos em tecido; Bordado; Textile crafts